Analysis of Psychological Portrait of Andrei Sheptytsky - Maslyuk, Andrew (Psychological Prospects Journal, 2018)
The historical-psychological analysis of the religious personality of Andriy Sheptytsky on the basis of the creative work of the Ukrainian diaspora scientist A. Kulchytsky was carried out. The figure of the metropolitan is viewed through the prism of opposing opposing points of view: hostile, hateful, and loving. Established a generalized psychological portrait of the metropolitan through the analysis of his inner world, thinking, perception, experiencing values. The personality of A. Sheptytsky is integral and unique, uniting in itself the service of God, the world and humanity. It was found that the main impetus of his activity was an internal religious motive. «Forget about yourself and know God» – this thesis is decisive in the spiritual life of the Metropolitan, who, by his own example, tried to inspire others to know God not only rational, but also intuitive means of knowledge. It was determined that A. Sheptytsky, as a patriot, called for the unification of the church, for the construction of a native home-homeland, which is based on christian values. The Metropolitan believed that without the christian faith, the formation of Ukrainian statehood, language, culture and traditions is impossible. The church should help concrete actions to develop Ukrainian statehood. The ideas of the Metropolitan on christian patriotism towards other nations were further developed. After all, christianity does not call for hostility among nations, but on the contrary, it demands that other nations and their traditions be treated with respect. christian patriotism is manifested in the fact that we love our Ukrainian people and are ready for it not only to lay down the work of our life, but also our very life. The Ukrainian national idea is enriched by a new approach based on «christian patriotism».